Influence of information technology on project risk management: The mediating role of risk identification - Qais Hammouri; Mohammad Alfraheed; Belal Mahmoud AlWadi; Amani Osman Sulieman Abdelrahman; Priti Mishra; Kais Khrouf; Mohamad Ahmad Saleem Khasawneh (Journal of Project Management)
This study investigates the critical role of information technology integration in enhancing project risk management, specifically examining the mediating effect of risk identification effectiveness. Based on a quantitative approach, the study collected data from 173 respondents working in the construction, engineering, and telecommunication sectors using a comprehensive questionnaire. We employed Smart PLS-SEM for data analysis to test the study hypotheses. Our findings reveal that IT integration significantly and positively influences both risk identification effectiveness and overall project risk management. Importantly, the study confirms the mediating role of risk identification effectiveness, indicating that IT's contribution to successful project risk management is significantly enhanced when it empowers teams to identify potential risks early and accurately. These findings indicate the strategic importance for organizations in these sectors to prioritize investments in IT solutions that not only streamline project management processes but also specifically enhance risk identification capabilities. Discussion and conclusion were depicted at the end of work.